Tenacibaculosis in aquaculture farmed marine fish - GOURZIOTI (Ε. ΓΟΥΡΖΙΩΤΗ) E.; KOLYGAS (M.N. ΚΟΛΥΓΑΣ) M. N.; ATHANASSOPOULOU (Φ. ΑΘΑΝΑΣΟΠΟΥΛΟΥ) F.; BABILI (Β. ΜΠΑΜΠΙΛΗ) V. (Journal of the Hellenic Veterinary Medical Society, 2018)
Tenacibaculosis is a limiting factor of the culture of many farmed marine fish worldwide. In marine fish species, the main etiological agent of the disease is the bacterium Tenacibaculum maritinun. The disease is responsible for high mortalities in intensive aquaculture farms. The infection can cause external pathological signs and lesions to the fish, such as ulcers, hemorrhagic and necrotic lesions on the skin, fins and tail, hemorrhagic stomatitis and corrosion of the tail and fins. In the present review information is provided regarding Tenacibaculum maritinun strains that infect farmed marine fish, the disease, the causative agent, host species, clinical symptoms, methods of diagnosis, pathogenesis of infection, the treatment and prevention of the disease.